Effectiveness of Zakah Targeting in Alleviating Poverty in Indonesia - Kasri, Rahmatina A (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2016)
Zakah is a unique Islamic institution targeted to eight groups of recipients with the aim to redistribute income, reduce poverty and achieve social welfare. However, the impacts and effectiveness of zakah targeting in reducing poverty is rarely measured. This is the main objective of the study. To achieve it, a survey was conducted to collect primary data from zakah recipients in Greater Jakarta Indonesia. The data were subsequently analysed by using descriptive and poverty index analyses. The main results suggest that the incidence, depth and severity of poverty amongst the recipients have decreased due to the contributions from zakah organizations. There are also indications that zakah has been distributed to the most disadvantaged people such as the uneducated and unemployed. The findings provide empirical evidence regarding positive contribution and effectiveness of zakah targeting in reducing poverty in Indonesia. Some policy implications of the findings are also highlighted to enrich discourses on the role of zakah in alleviating poverty in Muslim societies.DOI: 10.15408/aiq.v8i2.3005